2020
DOI: 10.1111/nph.16811
|View full text |Cite
|
Sign up to set email alerts
|

North American temperate conifer (Tsuga canadensis) reveals a complex physiological response to climatic and anthropogenic stressors

Abstract: Rising atmospheric CO 2 (c a) is expected to promote tree growth and lower water loss via changes in leaf gas exchange. However, uncertainties remain if gas-exchange regulation strategies are homeostatic or dynamical in response to increasing c a , as well as evolving climate and pollution inputs. Using a suite of tree ring-based δ 13 C-derived physiological parameters (Δ 13 C, c i , iWUE) and tree growth from a mesic, low elevation stand of canopy-dominant Tsuga canadensis in northeastern USA, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 155 publications
(267 reference statements)
0
6
0
Order By: Relevance
“…The increasing Δ 13 C trend was attributed to increases in stomatal conductance and A , and was interpreted as a recovery of tree physiology and growth from peak‐pollution levels, but, also in response to N status and warming growing season temperature. In one of the investigated sites in this study (ABP), acid deposition and soil biogeochemistry (Ca 2+ leaching) were shown to drive the increasing Δ 13 C trends after 1970 CE, albeit, to a lesser extent than soil moisture and VPD (Rayback et al, 2020). For some broadleaf species located in NE‐US, water availability was shown to override the effects of CO 2 , nitrogen, and acid deposition on leaf‐gas exchange and tree growth after 1980 CE (Levesque et al, 2017).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The increasing Δ 13 C trend was attributed to increases in stomatal conductance and A , and was interpreted as a recovery of tree physiology and growth from peak‐pollution levels, but, also in response to N status and warming growing season temperature. In one of the investigated sites in this study (ABP), acid deposition and soil biogeochemistry (Ca 2+ leaching) were shown to drive the increasing Δ 13 C trends after 1970 CE, albeit, to a lesser extent than soil moisture and VPD (Rayback et al, 2020). For some broadleaf species located in NE‐US, water availability was shown to override the effects of CO 2 , nitrogen, and acid deposition on leaf‐gas exchange and tree growth after 1980 CE (Levesque et al, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…Individual whole rings were separated using a razor blade under a microscope, and α‐cellulose was extracted from the wood samples following the protocol described by Leavitt and Danzer (1993). We measured δ 13 C from 1901 to 2012 at three sites including US‐Ha1 and US‐Ho1 (two flux tower sites at Harvard and Howland Forests, respectively) and ABP (Abbey Pond Forest, Rayback et al, 2020). We measured δ 13 C from 1992 to 2012 at eight additional sites to overlap with the common period of the longest flux‐tower record at Harvard Forest (US‐Ha1; Figure 1a; Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…It is worth mentioning that large uncertainties still exist with regard to sinks and fluxes in soils, vegetation and the associated boundary layer (e.g. Rayback et al ., 2020).…”
Section: Old Trees In a Changing Worldmentioning
confidence: 99%
“…CO2 enrichment experiments, eddy flux measurements, and remote sensing observations all show that increased atmospheric CO2 leads to increased water-use efficiency and net primary productivity, although the magnitude and duration of this fertilization effect varies (Walker et al 2020 ). Evidence from tree rings also finds increased water-use efficiency (via stable isotope studies), although more recently these estimates have been shown to be influenced by tree size and environmental factors (Marchand et al 2020 , Rayback et al 2020a ). In contrast, tree-ring evidence for a fertilization effect on radial tree growth is limited (Hickler et al 2008 , Girardin et al 2011 , 2016 , Frank et al 2015 , Giguère-Croteau et al 2019 , Hararuk et al 2019 ).…”
Section: Carbon Cycle Uncertainties Carbon Accounting and Atmospheric...mentioning
confidence: 99%